2005
DOI: 10.1016/j.jtcvs.2005.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical deterioration underlies malignant behavior of aneurysmal human ascending aorta

Abstract: The mechanical properties of the aneurysmal aorta deteriorate dramatically as the aorta enlarges, reaching critical levels associated with rupture by a diameter of 6 cm. This mechanical deterioration provides an explanation in engineering terms for the malignant clinical behavior (rupture and dissection) of the aorta at these dimensions. This work adds to our fundamental understanding of the biology of aortic aneurysms and promises to permit future application of engineering measurements to supplement aneurysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
129
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(152 citation statements)
references
References 14 publications
17
129
0
6
Order By: Relevance
“…7,8) Engineering calculations have estimated that as the aorta enlarges, distensibility of the aortic wall decreases, so that by approximately 6 cm, the aorta becomes rigid. 9) Consistent with this suggestion is the data from cases with Marfan's syndrome, [10][11][12][13] the aortopathy associated with bicuspid aortic valves (BAV) 14,15) and familial thoracic aortic aneurysms. 16) The majority of ATAA cases, however, are not due to Marfan's syndrome, aortopathy of BAV or familial/ genetic factors, but rather are usually ascribed to 'degenerative' factors and comprise 80% of all ATAA cases.…”
Section: Introductionmentioning
confidence: 85%
“…7,8) Engineering calculations have estimated that as the aorta enlarges, distensibility of the aortic wall decreases, so that by approximately 6 cm, the aorta becomes rigid. 9) Consistent with this suggestion is the data from cases with Marfan's syndrome, [10][11][12][13] the aortopathy associated with bicuspid aortic valves (BAV) 14,15) and familial thoracic aortic aneurysms. 16) The majority of ATAA cases, however, are not due to Marfan's syndrome, aortopathy of BAV or familial/ genetic factors, but rather are usually ascribed to 'degenerative' factors and comprise 80% of all ATAA cases.…”
Section: Introductionmentioning
confidence: 85%
“…Significant effort has been devoted to the investigation of the mechanical properties and pathogenesis of AsAA tissue (7,13,14,(18)(19)(20)(21); however, MFS-specific studies are scarce. A number of in vivo studies on Marfan tissues investigate aortic distensibility, stiffness index, and pulse wave velocity (3,(8)(9)(10)(11)(12), consistently finding increased aortic diameter (12), decreased distensibility (8)(9)(10), and stiffness (8,9,12) in MFS patients compared to age-and gender-matched controls; however, these parameters were not correlated, as also found in our study.…”
Section: In Vivomentioning
confidence: 99%
“…Regional aortic wall stiffness and size are considered to be coupled [6,12]. We previously showed that regional PWV had moderate to high specificity for predicting absence of increased in a total of 28 (14 %) segments (S1: 15 cases, S2: 6 cases, S3: 4 cases, S4: 2 cases, S5: 1 cases) ( Table 3).…”
Section: Pwv Valuesmentioning
confidence: 99%
“…It is expected that in TAA patients without Marfan syndrome, local aortic wall stiffness measured by PWV is increased. Interestingly, regional aortic wall stiffness and size are considered to be coupled [6,12]. However, the local aortic wall stiffness, measured by PWV in TAA patients, has not been reported before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation